2018
DOI: 10.1001/jama.2018.11785
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Syphilis Infection in Pregnant Women

Abstract: The USPSTF recommends early screening for syphilis infection in all pregnant women. (A recommendation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…We observed that 44.7% of our cohort lost systemic opportunities to prevent early infection for TPA; which supports the efforts pointed to serial serological tests among all the pregnancy and the perinatal study of the infants [17,18]. Additionally, newborns whose serologic tests for syphilis are reactive and whose mothers were treated for syphilis should undergo a comprehensive evaluation consisting of a detailed physical examination and close follow-up at three/ four and six months of age until VDRL/RPR reactivity declines or disappears [19].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 83%
“…We observed that 44.7% of our cohort lost systemic opportunities to prevent early infection for TPA; which supports the efforts pointed to serial serological tests among all the pregnancy and the perinatal study of the infants [17,18]. Additionally, newborns whose serologic tests for syphilis are reactive and whose mothers were treated for syphilis should undergo a comprehensive evaluation consisting of a detailed physical examination and close follow-up at three/ four and six months of age until VDRL/RPR reactivity declines or disappears [19].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 83%
“…The positive and negative predictive values depend on the population being tested and should be incorporated in the decision to treat. 35,36 Treponemal Evaluation of the placenta can be a useful adjunct to the diagnosis of syphilis. Grossly, the placenta appears hydropic and pale ( Figure 6).…”
Section: F I G U R E 4 Ultrasound Findings Of Fetal Syphilis A-e a mentioning
confidence: 99%
“…The diagnosis of syphilis in the neonate is similar to that used in the adult. Darkfield microscopy, PCR, or immunohistochemical stains of lesions, bodily fluid or neonatal tissue, including placenta can all be F I G U R E 5 A, Timeline of positivity for each serologic test component and B, comparison of traditional and reverse sequence algorithm 36,37,39 [Colour figure can be viewed at wileyonlinelibrary.com] used to confirm syphilis but are often not immediately available. 41 Similar to adults, the majority of neonates with CS will be asymptomatic.…”
Section: Neonatal Diagnosismentioning
confidence: 99%
“…The optimal approach to screening pregnant women for syphilis has not been established. Advantages and disadvantages to both the traditional and reverse-screening approach exist with regard to cost, laboratory throughput, false-positive rates, ability to discern previous or latent infection, and improved sensitivity for diagnosis of acute infection [ 7 , 15 , 17 ]. In addition, where syphilis PCR is available, lesions should be swabbed and tested for confirmatory diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…If untreated during pregnancy, maternal syphilis may result in fetal demise, or congenital infection, which may lead to severe physical and neurological disability or newborn death [ [3] , [4] , [5] , [6] ]. Key to prevention is screening pregnant women for syphilis at the initial prenatal visit, and if at increased risk, again in the third-trimester and at delivery [ 1 , 7 , 8 ]. The State of Ohio where our cases originated, requires syphilis screening of all pregnant women at the first antenatal visit but does not require repeat testing later in pregnancy nor at delivery [ 9 ].…”
Section: Introductionmentioning
confidence: 99%